One-step synthesis of magnetic hollow mesoporous silica (MHMS) nanospheres for drug delivery nanosystems via electrostatic self-assembly templated approach1. Issue 12 (11th February 2015) - Liu, Fang; Wang, Jingnan; Cao, Qingyun; Deng, Haidong; Shao, Guang; Deng, David Y. B.; Zhou, Wuyi
<x xml:space="preserve">Abstract</x> Yolk–shell magnetic hollow mesoporous silica nanospheres were synthesized in one-step via electrostatic self-assembly for controlled release in diagnosis and therapy.